JUSLIŠKUMO SAMPRATOS TRANSFORMACIJOS ŠIUOLAIKINĖJE FENOMENOLOGIJOJE. - Jonkus, Dalius (Problems / Problemos, 2012)
The question about transcendence in the contemporary phenomenology is related to the conception of sensibility. Michel Henry and Emanuel Levinas from one side and Aron Gurwitsch and Maurice Merleau-Ponty from the other side have totaly different understandings of sensibility. Analysing sensibility, Husserl elaborates a distinction between hyletic data and animating noesis. He claims that, from one side, hyle itself means nothing without intentional morfe, and, from the other side, the intuitive presentation of an object arises only on the basis of experienced complex of sensations. Michel Henry finds striking contrast between material and intentional phenomenology. He states that without pure impressions intentional phenomenology is impossible. According to him, Husserl gives preference to the intentional morfe and leaves behind the pure impression of sensuous hyletic data. Michel Henry's task is to rehabilitate material phenomenology, he stresses that sensuous data keeps the secret of primal experience. This turn to material phenomenology rehabilitates „immanence of life“ and creates new form of empiricism. Gurwitsch criticizes construction of hyle-morfe distinction. He claims that descriptive analysis of direct experience fails to ascertain such an intermediary stratum. Also phenomenological description demonstrates that sensibility is not a mediator between immanence and transcendence, but the domain of interaction between senses which create consciousness of meaning. My purpose is to show that this refutation of the hyle in general has important consequences. Phenomenology gives not only a redefinition of the concepts of noesis and intentionality, but also reforms the concept of time.